Optimization of the injection parameters of a diesel/natural gas dual fuel engine with multi-objective evolutionary algorithms - Liu, Jie; Zhao, Hongbo; Wang, Junle; Zhang, Ning (Applied thermal engineering, 2019)
•New gas/liquid dual fuel injection model was developed.•Multi-objective evolutionary algorithm is used to optimize the parameters.•NO formation follows the development of the high temperature field.•Soot formation is in the squish region. In this study, the injection parameters of a High-Pressure Direct-Injection (HPDI) natural gas engine was optimized by coupling a multi-dimensional computational fluid dynamics (CFD) code with the genetic algorithm (GA). Moreover, the analysis of the combustion and emission characteristics of a diesel/natural gas dual fuel engine are performed in this paper with the introduction of the diesel/natural gas dual fuel injection model into the CFD code. The result reveals that the developed gas fuel injection model is capable to predicate the penetrations of the natural gas injection. For the dual fuel engine with simultaneous reduction of NOx and soot, the optimized diesel injection timing is at −15.2 °CA ATDC, the gas injection timing is around −6.0 °CA ATDC, and the circumferential offset angle between the diesel and natural gas nozzle hole is around 8.8°. The lowest ISFC condition is achieved when the injection interval between the diesel and natural gas is 1.38 °CA. For the high soot emissions cases, the gas injection timings are later compared with the other cases. In the dual fuel engine, most of the NO emissions are generated through the combustion of the direct injected natural gas. Soot formation region is mainly located in the squish volume close to the cylinder walls, where the temperature is low which leads to a lower soot oxidation rate.